Optimal cut‐off value of fecal calprotectin for the evaluation of ulcerative colitis: An unsolved issue?. Issue 5 (10th August 2018) - Jha, Ashish Kumar; Chaudhary, Madhur; Dayal, Vishwa Mohan; Kumar, Amarendra; Jha, Sanjeev Kumar; Jha, Praveen; Purkayastha, Shubham; Ranjan, Ravish
Abstract : Introduction: There is variability in the fecal calprotectin (FCP) cut‐off level for the prediction of ulcerative colitis (UC) disease activity and differentiation from irritable bowel disease (IBS‐D). The FCP cut‐off levels vary from country to country. Aims: We aimed to assess FCP as a marker of disease activity in patients with UC. We determined the optimal FCP cut‐off value for differentiating UC and IBS‐D. Methods: In a prospective study, we enrolled 76 UC and 30 IBS‐D patients. We studied the correlation of FCP with disease activity/extent as well as its role in differentiating UC from IBS‐D. We also reviewed literature regarding the optimal FCP cut‐off level for the prediction of disease activity and differentiation from IBS‐D patients. Results: Sensitivity, specificity, positive predictive value, and negative predictive value of FCP (cut‐off level, 158 μg/g) for the prediction of complete mucosal healing (using Mayo endoscopic subscore) were 90, 85, 94.7, and 73.3%, respectively. Sensitivity, specificity, positive predictive value, and negative predictive value of FCP (cut‐off level, 425 μg/g) for the prediction of inactive disease (Mayo Score ≤ 2) were 94.3, 88.7, 86.2, and 95.4%, respectively. We also found a FCP cut‐off value of 188 μg/g for the differentiation of UC from IBS‐D. Conclusions: The study reveals the large quantitative differences in FCP cut‐off levels in different study populations. This study demonstrates a wide variation in FCP cut‐off levels in the initial diagnosis of UC as well as in follow‐up post‐treatment. Therefore, this test requires validation of the available test kits and finding of appropriate cut‐off levels for different study populations. Abstract : There is a lack of agreement on the best cut‐off levels of fecal calprotectin (FCP) to differentiate inflammatory bowel disease (IBD) from IBS, and for predicting endoscopic activity, remission, and relapse. Due to a wide variation in cut‐off level proposed in various studies, the FCP test requires validation of the available test kits and finding of the appropriate cut‐off level for different study populations.